1983
DOI: 10.1073/pnas.80.4.1092
|View full text |Cite
|
Sign up to set email alerts
|

Vibrio cholerae hemagglutinin/lectin/protease hydrolyzes fibronectin and ovomucin: F. M. Burnet revisited

Abstract: Cholera vibrios produce a single polymeric protein that (i) causes hemagglutination; (ii) appears to participate in their attachment to gut epithelium; (iii) may mediate their detachment from gut epithelium; and (iv) is a protease that hydrolyzes fibronectin and mucin, cleaves lactoferrin, and nicks the A subunit of the choleragen-related heat-labile enterotoxin of Escherchia coli.In 1947, F. M. Burnet reported the discovery of a mucinase, elaborated by Vibrio cholerae, which participated in the desquamation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
136
1

Year Published

1985
1985
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(141 citation statements)
references
References 36 publications
2
136
1
Order By: Relevance
“…Moreover, gbpA mutants display defects in adherence to human epithelial cells and in colonization of infant mice, suggesting that GbpA represents a dual colonization factor functioning both in the aquatic environment and the human host (27). Similarly, HAP has been suggested to play a role in infection by facilitating the penetration of V. cholerae through the mucus barrier of the gastrointestinal tract and by causing its detachment from the epithelium following the induction of the secretory diarrhea (37,38).…”
mentioning
confidence: 99%
“…Moreover, gbpA mutants display defects in adherence to human epithelial cells and in colonization of infant mice, suggesting that GbpA represents a dual colonization factor functioning both in the aquatic environment and the human host (27). Similarly, HAP has been suggested to play a role in infection by facilitating the penetration of V. cholerae through the mucus barrier of the gastrointestinal tract and by causing its detachment from the epithelium following the induction of the secretory diarrhea (37,38).…”
mentioning
confidence: 99%
“…Consistently, inactivation of hapA encoding HA/protease enhances adherence to mucin-coated polystyrene plates , adherence to mucin-secreting differentiated HT29-18N2 cultured cells (Benitez et al, 1997), and colonization of the suckling mouse intestine (Robert et al, 1996;Silva et al, 2006). The mucinase activity of HA/protease (Finkelstein et al, 1983), together with its capacity to cleave the mucin-binding adhesin GbpA (Jude et al, 2009) at high cell density, has provided a mechanism supporting the "detachase" function attributed to this protein.…”
Section: Hemagglutinin/proteasementioning
confidence: 80%
“…Numerous V. cholerae strains of the El Tor biotype express a Zn-dependent metalloprotease (mucinase) known as hemagglutinin (HA)/protease (Finkelstein et al, 1983;Hase & Finkelstein, 1991). HA/protease enhances enterotoxicity in the rabbit ileal loop model of cholera (Ichinose et al, 1994;Silva et al, 2006) and contributes to live vaccine candidates' reactogenicity in humans (Benitez et al, 1999;Garcia et al, 2005).…”
Section: Hemagglutinin/proteasementioning
confidence: 99%
“…Likewise, in the present experiment the caseinolytic as well as HA activities of TEP-inactivated proteases could be reversed by the addition of trace amounts of metal ions. The effect of proteolysis on the HA activities were shown with V cholerae protease (VCP) and VMP (3,5). Based on this data which demonstrated the simultaneous inactivation and reactivation of both caseinolytic and HA activities, it can be concluded that the proteolytic enzymes produced by the above vibrios also possess HA ability.…”
mentioning
confidence: 92%
“…Of these, the protease from Vibrio cholerae (5) is well known for its roles in the pathogenesis of deadly cholera (2,4). This protease was first discovered as an adhesion factor due to its hemagglutinating (HA) abilities (6), and was then shown to be a protease (5) possessing the ability to nick and activate the cholera enterotoxin (2). Later, it was demonstrated to be a metalloprotease containing zinc as an essential ligand (1).…”
mentioning
confidence: 99%